A novel bio-electro-Fenton process for eliminating sodium dodecyl sulphate from wastewater using dual chamber microbial fuel cell. (December 2021) - Sathe, S.M.; Chakraborty, Indrajit; Sankar Cheela, V.R.; Chowdhury, Shamik; Dubey, B.K.; Ghangrekar, M.M.
Graphical abstract: Highlights: Bio-electro-Fenton-MFC (BEF-MFC) for degradation of sodium dodecyl sulphate (SDS) Superior performance of BEF-MFC than non-catalysed MFC. SDS removal of 87.4 ± 2.2% using BEF-MFC in 4 h of contact time. First Life cycle assessment (LCA) of BEF-MFC. Low environmental impacts of BEF-MFC based on LCA. Abstract: The frequent occurrence of surfactants in urban wastewaters represents a multifaceted environmental concern. In this investigation, bio-electro-Fenton-microbial fuel cell (BEF-MFC) was developed for the degradation of sodium dodecyl sulphate (SDS) from wastewater. The synthesised cathode catalyst (powdered activated carbon and iron oxide) facilitated the Fenton reaction in the cathodic chamber of the MFC, concurrently generating a maximum power density of 105.67 mW m −2 . The overall performance of the BEF-MFC for SDS removal and power generation excelled the control MFC (C-MFC) having carbon black coated cathode under similar operating conditions. Although, the rate of SDS degradation was favourable in acidic pH, under neutral pH, 70.8 ± 6.4% of SDS degradation was achieved in 120 min in BEF-MFC. A comparison of environmental impacts of BEF-MFC with up-flow MFC and electrochemical oxidation using life cycle assessment tool suggests that BEF-MFC can be one of the promising technologies for the tertiary treatment of wastewater.